Characterisation of the rural indigent population in Burkina Faso: a screening tool for setting priority healthcare services in sub-Saharan Africa - Ouédraogo, Samiratou; Souares-Coutant, Aurélia (BMJ open, 2017)
Background In Africa, health research on indigent people has focused on how to target them for services, but little research has been conducted to identify the social groups that compose indigence. Our aim was to identify what makes someone indigent beyond being recognised by the community as needing a card for free healthcare. Methods We used data from a survey conducted to evaluate a state-led intervention for performance-based financing of health services in two districts of Burkina Faso. In 2015, we analysed data of 1783 non-indigents and 829 people defined as indigents by their community in 21 villages following community-based targeting processes. Using a classification tree, we built a model to select socioeconomic and health characteristics that were likely to distinguish between non-indigents and indigents. We described the screening performance of the tree using data from specific nodes. Results Widow(er)s under 45 years of age, unmarried people aged 45 years and over, and married women aged 60 years and over were more likely to be identified as indigents by their community. Simple rules based on age, marital status and gender detected indigents with sensitivity of 75.6% and specificity of 55% among those 45 years and over; among those under 45, sensitivity was 85.5% and specificity 92.2%. For both tests combined, sensitivity was 78% and specificity 81%. Conclusion In moving towards universal health coverage, Burkina Faso should extend free access to priority healthcare services to widow(er)s under 45, unmarried people aged 45 years and over, and married women aged 60 years and over, and services should be adapted to their health needs. Ethics considerations The collection, storage and release of data for research purposes were authorised by a government ethics committee in Burkina Faso (Decision No. 2013-7-066). Respondent consent was obtained verbally.
Gesehen am 25.04.2018